Delayed Diagnosis of Psoriatic Arthritis Mutilans due to Arthritis Prior to Skin Lesion - Takeshi Mochizuki; Katsunori Ikari; Ken Okazaki (Case Reports in Rheumatology)
Psoriatic arthritis (PsA) is a type of inflammatory arthritis characterized by cutaneous psoriasis, peripheral joint damage, axial joint damage, and enthesitis and is usually diagnosed after the appearance of psoriatic skin disease. PsA mutilans is relatively rare in Japan. In the present case, the patient was diagnosed with PsA with foot mutilans deformity only. Hand and spinal radiograph findings were unremarkable. As in the present case arthritis is occurred prior to the onset of skin lesion, we should make early diagnosis to prevent mutilans deformity.